N-Acyl-Homoserine Lactone Primes Plants for Cell Wall Reinforcement and Induces Resistance to Bacterial Pathogens via the Salicylic Acid/Oxylipin Pathway . Issue 6 (24th June 2014) - Schenk, Sebastian T.; Hernández-Reyes, Casandra; Samans, Birgit; Stein, Elke; Neumann, Christina; Schikora, Marek; Reichelt, Michael; Mithöfer, Axel; Becker, Annette; Kogel, Karl-Heinz; Schikora, Adam
Abstract : The bacterial quorum-sensing molecule N -3-oxo-tetradecanoyl-l -homoserine lactone primes the plant for enhanced resistance to bacterial pathogens. The proposed mechanism is based on modifications of the cell wall composition and the responsiveness of stomatal guard cells to pathogen attack. Abstract: The ability of plants to monitor their surroundings, for instance the perception of bacteria, is of crucial importance. The perception of microorganism-derived molecules and their effector proteins is the best understood of these monitoring processes. In addition, plants perceive bacterial quorum sensing (QS) molecules used for cell-to-cell communication between bacteria. Here, we propose a mechanism for how N -acyl-homoserine lactones (AHLs ), a group of QS molecules, influence host defense and fortify resistance in Arabidopsis thaliana against bacterial pathogens. N -3-oxo-tetradecanoyl-l -homoserine lactone (oxo-C14-HSL ) primed plants for enhanced callose deposition, accumulation of phenolic compounds, and lignification of cell walls. Moreover, increased levels of oxylipins and salicylic acid favored closure of stomata in response to Pseudomonas syringae infection. The AHL -induced resistance seems to differ from the systemic acquired and the induced systemic resistances, providing new insight into inter-kingdom communication. Consistent with the observation that short-chain AHLs, unlike oxo-C14-HSL, promote plant growth, treatments with C6-HSL, oxo-C10-HSL, or oxo-C14-HSL resulted in different transcriptional profiles in Arabidopsis . Understanding the priming induced by bacterial QS molecules augments our knowledge of plant reactions to bacteria and suggests strategies for using beneficial bacteria in plant protection.